2009
DOI: 10.1186/1741-7015-7-81
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the potential for within-flight transmission of influenza A (H1N1)

Abstract: BackgroundClearly air travel, by transporting infectious individuals from one geographic location to another, significantly affects the rate of spread of influenza A (H1N1). However, the possibility of within-flight transmission of H1N1 has not been evaluated; although it is known that smallpox, measles, tuberculosis, SARS and seasonal influenza can be transmitted during commercial flights. Here we present the first quantitative risk assessment to assess the potential for within-flight transmission of H1N1.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 14 publications
3
69
0
4
Order By: Relevance
“…An infectious quantum is defined as the dose of droplet nuclei required to cause infection in 63% of susceptible persons. Quanta production rates of infectious individuals have been retrospectively calculated by several epidemiological studies of influenza outbreaks, and we used a value of 67 quanta/h, which represents the approximate median of infectivity estimates for both seasonal influenza [11] and H1N1 [12]. Furthermore, we used the full range of published values; 15 to 128 quanta/h [13], in order to establish the likely range of risk in our simulations.…”
Section: Discussionmentioning
confidence: 99%
“…An infectious quantum is defined as the dose of droplet nuclei required to cause infection in 63% of susceptible persons. Quanta production rates of infectious individuals have been retrospectively calculated by several epidemiological studies of influenza outbreaks, and we used a value of 67 quanta/h, which represents the approximate median of infectivity estimates for both seasonal influenza [11] and H1N1 [12]. Furthermore, we used the full range of published values; 15 to 128 quanta/h [13], in order to establish the likely range of risk in our simulations.…”
Section: Discussionmentioning
confidence: 99%
“…tested in 14 different daycare centres, Boone & Gerba [9] detected influenza viruses on 23 and 53 per cent of the samples during autumn and spring, respectively. Infected individuals on an aeroplane may spread the influenza virus to other passengers [10]. The Alaska Airlines outbreak [11] has been presented as proof of airborne influenza transmission: a jet with 54 persons aboard was delayed on the ground for 3 h (during which the aeroplane ventilation system was inoperative), and 72 per cent of the passengers who stayed on the aeroplane were infected by an influenza-contracted passenger within 72 h.…”
Section: Introductionmentioning
confidence: 99%
“…In 1988, Brundage et al [8] showed that febrile illness rates were about 50% higher in sealedwindow than in operable window army barracks. Wagner et al [9] estimated that one passenger infected with H1N1 and travelling in economy class of a commercial aircraft may cause two to five infections during a 5 hour flight and a 5-10 during an 11 hour flight. There are also other studies that analyze experimentally and numerically the airborne pollutant transport within aircrafts (see for example, Liu et al [10], Zhang et al [11], Mazumdar and Chen [12]).…”
Section: Introductionmentioning
confidence: 99%